GAME MACHINE - KONDO KENGO (2023)
To increase the interest of a game.SOLUTION: A game machine comprising display means and operation means that is provided operable by a player and for shooting a game ball into a game area with a shooting intensity corresponding to an operation by the player can execute a shooting intensity display performance for displaying the shooting intensity of the game ball shot in the game area on the display means.SELECTED DRAWING: Figure 24 【課題】遊技の興趣を向上させることを目的とする。【解決手段】表示手段と、遊技者によって操作可能に設けられ、遊技者による操作に応じた発射強度で遊技球を遊技領域へ射出するための操作手段と、を備える遊技機において、遊技領域へ射出されている遊技球の発射強度を表示手段に表示する発射強度表示演出を実行可能である。【選択図】図２４